2016
DOI: 10.1111/bjh.14145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of B cell maturation antigen as a target for antibody drug conjugate mediated cytotoxicity in multiple myeloma

Abstract: B-cell maturation antigen (BCMA, also termed TNFRSF17) is an attractive therapeutic target due to its restricted expression on normal and malignant plasma cells (PC). GSK2857916 (or J6M0-MMAF) is a BCMA-specific antibody conjugated to the microtubule-disrupting agent monomethyl auristatin F (MMAF) via a protease-resistant linker. To evaluate the clinical potential of this agent, tumour cells from seventy multiple myeloma (MM) patients were assessed for BCMA expression by immunohistochemistry and flow cytometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
121
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(149 citation statements)
references
References 26 publications
13
121
1
2
Order By: Relevance
“…These investigators reported that all patient samples tested were BCMA+ and found a mean of 1,085 BCMA molecules per MM cell (range 349-4,268). 41 These values are well in the range of the reactivity of the anti-BCMA CAR T cells in this study, which it was demonstrated recognized BCMA+ cell lines that expressed as little as 222 BCMA molecules per cell (Table 1 and Fig. 4).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…These investigators reported that all patient samples tested were BCMA+ and found a mean of 1,085 BCMA molecules per MM cell (range 349-4,268). 41 These values are well in the range of the reactivity of the anti-BCMA CAR T cells in this study, which it was demonstrated recognized BCMA+ cell lines that expressed as little as 222 BCMA molecules per cell (Table 1 and Fig. 4).…”
Section: Discussionsupporting
confidence: 81%
“…38,39 BCMAtargeting antibody drug conjugates (ADC), bispecific BCMA/CD3 antibodies, and BCMA-targeted CAR T cells have all been reported to have anti-MM cell reactivity. 23,26,40,41 Recently, in a study of anti-BCMA bi-specific antibodies, Lee et al used ABCbead quantitation methods to determine BCMA receptor density on 39 MM patient samples. These investigators reported that all patient samples tested were BCMA+ and found a mean of 1,085 BCMA molecules per MM cell (range 349-4,268).…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al [25] • BM aspirates collected from pts with ND or RRMM, assessed for BCMA expression by FC…”
Section: Resultsmentioning
confidence: 99%
“…BCMA is highly expressed on malignant PCs collected from patients with MM compared with normal bone marrow mononuclear cells (BMMCs) from healthy donors, and several studies have assessed whether BCMA has value as a marker for diagnosis, prognosis, and/or as a predictor of treatment response (Table 1) [7,[23][24][25][26][27][28]. In contrast with CD138, BCMA is readily identified in delayed and frozen MM samples [22].…”
Section: Bcma As a Biomarker For Diagnosis Of MMmentioning
confidence: 99%
“…Toward the goal of dual-antigen targeting for MM, a CAR incorporating a truncated "a proliferation-inducing ligand" (dAPRIL) as the ligand-binding domain had previously been reported to interact with both BCMA and another MM marker, the transmembrane activator and CAML interactor (TACI) 13 . However, TACI, like BCMA, exhibits heterogeneous expression in MM, and MM cells lacking expression of both antigens have been previously identified [14][15][16] . In contrast, CS1 (also known as SLAMF7 or CD319) is highly expressed on multiple types of MM and has been found on 90-97% of patient MM samples 17,18 , and an anti-CS1 CAR-T cell therapy 19 is currently being tested in the clinic (NCT03710421).…”
mentioning
confidence: 99%